Tobacco Cessation Objective Structured Clinical Examination (OSCE) - David Brown; Alex Mechaber; Ed Trapido; Mary Mites Campbell; Erin Marcus; Asma Aftab; Robert Hernandez; Mark OConnell (Association of American Medical Colleges, 2009)
Abstract This objective structured clinical examination (OSCE) station was developed to evaluate the motivational interviewing and counseling skills of medical students at the end of the third year. It assesses the skills recommended in the US Public Health Service guidelines for treating tobacco dependence and includes instructions for students, standardized patients (SPs), and evaluators. Tobacco dependence is the number one preventable cause of death, killing half of its continuing users. Based on the chronic care model, the US Public Health Service published detailed, evidence-based guidelines (the "5 A's") for physician intervention, updated in 2008. This OSCE station provides the opportunity to evaluate the knowledge, attitudes, and skills required to implement these guidelines. This module requires a SP and observer to evaluate students. Fifteen minutes is required per student for testing and evaluation. Patients and observers should not prompt students beyond instructions provided. Both patients and evaluators should be trained to promote consistency.